Implementation of Criminal Law to Sexual Violence - Shinta Rahmalia Saputri (Proceeding International Conference Restructuring and Transforming Law, 2024)
Sexual violence is a very serious crime and has adverse consequences for victims. From the results of data recorded in the National Commission on Violence against Women, there were 312,461 incidents of violence against women in Indonesia in 2022. Although sexual violence can happen to anyone, whether children, women, or men, children and women are the most vulnerable groups to sexual violence. The application of criminal law in dealing with sexual violence is a crucial step. Criminal law is able to provide a deterrent effect on perpetrators, protect victims, and restore their rights. The application of criminal law in handling sexual violence crimes in Indonesia is described in Law Number 12 of 2022 concerning Sexual Violence Crimes, a new law passed in 2022. This law presents several new, more progressive provisions in an effort to deal with sexual violence crimes.